Nanofluid Electrolyte with Fumed Al2O3 Additive Strengthening Zincophilic and Stable Surface of Zinc Anode toward Flexible Zinc–Nickel Batteries. (27th December 2022) - Luan, Jingyi; Yuan, Hongyan; Wang, Haozhi; Zhao, Naiqin; Zhong, Cheng; Lu, Jun
Abstract: Flexible zinc–nickel batteries (FZNBs) have been considered as a promising power supply for wearable electronics due to the intrinsic safety, high operating voltage and superior rate performance. However, the serious self‐corrosion of zinc and the redistribution of dissolved [Zn(OH)4 ] 2− on the electrode surface limit the electrochemical performance of FZNBs. Herein, the nanofluid electrolyte with fumed Al2 O3 additive is introduced into FZNBs and a protective layer is formed due to the adsorption of Al2 O3 on the electrodeposited zinc anode. The protective layer strengthens the zincophilicity of the anode and homogenizes the deposition of [Zn(OH)4 ] 2−, avoiding the dendrite formation and the shape change of electrode. Meanwhile, by suppressing the [Zn(OH)4 ] 2− diffusion from the anode surface to the bulk electrolyte, the interface stabilization is effectively promoted, thereby improving zinc utilization rate and inhibiting the corrosion. Hence, the FZNBs assembled with Al2 O3 ‐nanofluid electrolyte and electrodeposited zinc anode demonstrates superior energy density of 210 Wh L −1 with a stable cycling of 575 h. Furthermore, FZNBs modified with Al2 O3 ‐nanofluid electrolyte have a promising future in the field of wearable and portable electronics. Abstract : The Al2 O3 ‐nanofluid electrolyte is introduced into flexible zinc–nickel battery and a protective layer is spontaneously formed on the electrodeposited zinc anode, which not only acts as the zincophilic sites to induce uniform deposition of [Zn(OH)4 ] 2− and avoid the shape change of electrode, but also effectively suppresses the diffusion of [Zn(OH)4 ] 2− to inhibit the corrosion of zinc.